Severe dengue fever presented as acute necrotizing encephalopathy with multiple organ dysfunction syndrome: a case report - Saini, Susheel Kumar; Maheshwari, Prabhat; Garg, Palak; Kumari, Seema; Saini, Ajay Kumar (International Journal of Contemporary Pediatrics, 2022)
Acute necrotizing encephalopathy (ANE) is a para-infectious, pauci-inflammatory disorder predominantly reported among children younger than 5 years of age. The diagnosis is based on the typical clinical presentation, imaging findings, and exclusion of other mimicking conditions.Although the pathophysiology of ANE is not completely understood, it is considered to be immune-mediated after a viral infection. Neurological manifestations of dengue are increasingly being recognized. These include encephalopathy, encephalitis, myelitis, myositis, Guillain-Barre syndrome and mononeuropathies. ANE following dengue fever has been reported earlier but rarely. We present a case of a boy who developed this condition with classical clinico-radiologic findings of ANE secondary to severe dengue infection. He had a stormy hospital course but survived without sequelae. We report this case with the aim to raise awareness about this fatal neurological complication of dengue infection as dengue has become a global health-care problem.